The Strategy of Islamic Religious Counselors in Fostering Religious Spirit among the Community in Balassuka Village, Tombolo Pao Sub-District - Harlina; Muliaty Amin; Nasriah (Jurnal Mercusuar, 2023)
The main problem in this research is the strategy of Islamic religious counselors in fostering the religious spirit of the community in Dusun Benga, Balassuka Village, Tombolo Pao Subdistrict. From this main problem, the researcher formulates three sub-problems, namely the strategies for fostering the religious spirit by religious counselors. This research is qualitative in nature and utilizes the approach of preaching (dakwah) and communication. The data sources for this research are primary data from religious counselors, community leaders, and local government, using research methods such as observation, interviews, and documentation. The results of this research indicate that the strategies for fostering the religious spirit in the Benga hamlet include: Islamic preaching (Tablig Islam), organization development/PMI (takwin), and institution management (tadbir). The implications of this research are: 1. Encouraging the community to be more open to receiving religious preaching. 2. Advising religious counselors to enhance their personal qualities and expand the scope of their guidance. 3. Urging the government to pay more attention to factors hindering preaching activities.